UNIT 9.21 Functional Studies of Sodium Channels: From Target to Compound Identification. Issue 1 (13th December 2016) - Bertrand, Daniel; Biton, Bruno; Licher, Thomas; Chambard, Jean‐Marie; Lanneau, Christophe; Partiseti, Michel; Lefevre, Isabel A.
Abstract : Over the last six decades, voltage‐gated sodium (Nav ) channels have attracted a great deal of scientific and pharmaceutical interest, driving fundamental advances in both biology and technology. The structure and physiological function of these channels have been extensively studied; clinical and genetic data have uncovered their implication in diseases such as epilepsy, arrhythmias, and pain, bringing them into focus as current and future drug targets. While different techniques have been established to record the activity of Nav channels, proper determination of their properties still presents serious challenges, depending upon the experimental conditions and the desired subtype of channel to be characterized. The aim of this unit is to review the characteristics of Nav channels, their properties, the cells in which they can be studied, and the currently available techniques. Topics covered include the determination of Nav ‐channel biophysical properties as well as the use of toxins to discriminate between subtypes using electrophysiological or optical methods. Perspectives on the development of high‐throughput screening assays with their advantages and limitations are also discussed to allow a better understanding of the challenges encountered in voltage‐gated sodium channel preclinical drug discovery. © 2016 by John Wiley & Sons, Inc.